2015
DOI: 10.2495/eq-v1-n1-72-86
|View full text |Cite
|
Sign up to set email alerts
|

A suggested roadmap for world-wide energy resource planning and management

Abstract: In the near future, we will need an internationally based system for worldwide planning of future energy resources and their effect on the world environment. Logically, this should be a responsibility of the United Nations, which already possesses much of the infrastructure needed and is already active in this area. Because different nations have different resources, different problems and different needs, it is reasoned that a flexible and diplomatic approach is also called for. We will need to try to secure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The enormous resulting fireball would have no effect on the underground reactor which would be expected to continue functioning normally. For the nuclear complex (described in the present paper and outlined in the earlier ones [4,5]) it is suggested that the whole complex be declared a registered 'no fly zone'. Anti-aircraft missiles could be programmed to destroy any airborne intruder automatically.…”
Section: Protecting Msrs From Acts Of Terrorismmentioning
confidence: 99%
See 2 more Smart Citations
“…The enormous resulting fireball would have no effect on the underground reactor which would be expected to continue functioning normally. For the nuclear complex (described in the present paper and outlined in the earlier ones [4,5]) it is suggested that the whole complex be declared a registered 'no fly zone'. Anti-aircraft missiles could be programmed to destroy any airborne intruder automatically.…”
Section: Protecting Msrs From Acts Of Terrorismmentioning
confidence: 99%
“…REACTOR (FSMSR) Whereas the research at Oak Ridge gave sufficient data and experience for designing a thermal MSR [4,5], the design of a fast neutron spectrum FSMSR, without similar previous practical experience, is a much more daunting task. Yet fundamentally the fast reactor is a much more simple device.…”
Section: Developing a Fast Neutron Spectrum Molten Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in an earlier paper [10], the whole family of different MSRs provides a comprehensive and integrated system for providing our base-load energy needs in a fully closed cycle that also deals with the long-term problem of nuclear waste disposal. Thorium fuel reserves alone are sufficient for 1,000 years.…”
Section: Introductionmentioning
confidence: 99%
“…E.g., new techniques are emerging for electricity accumulation and storage, long-range wireless power transfer, remote monitoring and service of energy equipment (Gudmestad and Traa [6], Boothroyd [7]). …”
Section: Introductionmentioning
confidence: 99%